Agricultural Land Use and Rural Development - Zhang, Xueru (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Agricultural land provides essential goods and services for human society, and it is the basis for ensuring food security and rural development. Under the background of rapid urbanization, population growth, and climate change, the use of agricultural land has intensified and changed on local, regional, and global scales. Although these changes have met the growing food demand and adjusting dietary structure to some extent, they have also led to negative impacts such as deforestation, wetland reduction, water pollution and shortages, and soil degradation. In addition, the change in agricultural land use is not only a driving factor but also a result of rural development, especially in developing countries. Driven by urbanization and economic development, a large amount of agricultural land has been occupied by urban sprawl and a large number of rural laborers have migrated to cities, resulting in the abandonment of marginal cropland, the non-agricultural and non-grain use of high-quality cropland, as well as crop type changes. Optimizing the trade-offs and synergies between agricultural production, farmers' livelihoods, and ecological protection has become the scientific basis for rural revitalization and sustainable development. Therefore, it is critical to systematically study the changes in agricultural land use and rural development as well as their interaction, providing scientific and practical implications for food security and sustainable rural management.